Study the Effect of Using Microwave Energy in Chemical Processes for Dyeing and Printing Pretreatments of Cotton Fabrics - Almirdash, Lina Mohammad; Saffour, Ziad (Al-Nahrain Journal for Engineering Sciences, 2019)
The research focuses on studying the effect of microwave energy as an alternative heating method on dyeing and printing pretreatments of cotton fabrics. In this research, a microwave oven was used to heat the solutions which used in de-sizing, scouring, bleaching and mercerizing processes at different energy levels. The results showed the importance of this heating method in improving desizing efficiency where the best result was obtained at 180 W and 24 min and this method was beneficial in saving energy and time. The best result in scouring was obtained at 720 watts and 24 minutes, whereas at 720 watts and 20 minutes was the best result in bleaching. We can save energy, time and chemicals compared with the conventional method. The mercerizing by microwave increased the absorption of dye solutions for the samples compared with the traditional method, where the color strength increased by increasing the treatment time and the level of energy in the microwave and the best result was obtained at 900 watts and 90 seconds.